Clinical and Functional Outcomes Associated with Age after Transapical Transcatheter Aortic Valve Replacement. Issue 2 (March 2019) - Okoh, Alexis Kofi; Kang, Nathan; Haik, Nicky; Fugar, Setri; Chunguang, Chen; Bruce, Haik; Cohen, Marc; Russo, Mark J.
Abstract : Objective: Transcatheter aortic valve replacement (TAVR) via a transapical (TA) approach has been associated with high morbidity. The aim of this study is to investigate the association of age and clinical and functional outcomes after TA-TAVR. Methods: Patients who had TA-TAVR at a single center were divided into 3 age groups: <75 years (Group I), 75 to 85 years (Group II), and >85 years (Group III). Pre- and postoperative clinical, functional status, and procedure-related outcomes were compared among patient groups. A multivariable Cox proportional hazards model was used to assess the impact of age on overall all-cause mortality. Results: Out of 183 TA-TAVR cases performed, 117 met the study criteria. These included 15 aged <75 years, 60 aged 75 to 85 years, and 42 aged >85 years. Short-term (30-day) clinical and functional status improved significantly for all age groups. The incidence of acute kidney injury, access site complications, and requirement for permanent pacemaker were similar for all age groups at 30 days. After a median follow-up of 26 months, overall all-cause survival rates were 86% for Group I, 88% for Group II, and 83% for Group III at 1 year. Cox proportional hazards model showed frailty status (HR: 1.84; 95% CI, 1.23 to 2.69; P = 0.003) but not age as an independent predictor of overall all-cause mortality. Conclusions: Findings from this study suggest that both older and younger patients benefit from TA-TAVR with comparable operative outcomes. Age should not be an exclusion criterion for TA-TAVR.